Access control model for multi-source heterogeneous data in big data environment - Qiuyue SU; Xingshu CHEN; Yonggang LUO (网络与信息安全学报)
The big data platform is open and shared,but with the increasing amount of data and the complex and variable user access context,the RBAC model is difficult to meet the fine-grained and flexible access control in big data environment.To solve this problem,an access control model for multi-source heterogeneous data in big data platform is proposed.The model dynamically determines role permissions based on attributes and builds a hierarchical structure based on data groups to achieve simple management of data attributes.The model is formally defined,and the implementation and workflow in Hadoop platform are described.The experimental results show that the performance overhead of the proposed scheme is relatively small.